Optimal solar panel placement in mobile edge computing. (22nd June 2021) - Vaezpour, Seyed Yahya
Mobile edge computing (MEC) enhances smart phone computational and storage capabilities by offloading tasks from mobile phones to the edge of the network where servers are placed near base stations. Since data centres consume electricity more and more each year, we consider locating renewable energy sources such as solar panels near each MEC. We tackle these challenges by strategically placing solar panels near MECs to minimise the energy costs. We formulate and solve the optimisation problem and present two algorithms to solve the optimisation problem. Moreover, we analyse the workload of each MEC during past years, and we present an algorithm to predict future workload of different MECs. We evaluate our solution using real Google traces collected over a 29-day period from a Google cluster. Simulation results show that with the help of our optimisation algorithms, we can effectively reduce the electricity costs and increase the green energy consumption.